BARRAGE LASER PHOTOCOAGULATION IN HIGH-MYOPIC PATIENT WITH SYMPTOMATIC RETINAL TEARS BEFORE PHACOEMULSIFICATION: A CASE REPORT: Poster Presentation - Case Report - Ophthalmologist - Budhiastra, I Putu; Tridiyoga, Komang Putra; Jayanegara, I wayan Gede; Suryathi, Ni Made Ari; Andayani, Ari; Pitanatri, Nyoman Brahmani (Majalah Oftalmologi Indonesia, 2023)
Introduction : Retinal tears can be present in up to 2.4% of cases of lattice degeneration, which is considered an important risk of retinal detachment in a high-myopic patient. Laser photocoagulation has been shown to reduce the risks of retinal detachment before phacoemulsification thus improve in the visual outcome. We report a case of a high myopic patient with symptomatic retinal tears who underwent phacoemulsification that was treated prophylactically with barrage laser photocoagulation. Case Illustration : A 43 years-old female with a history of high myopia complained of flashes and floaters on both eyes. She had high myopia measuring -13.0 dioptres and -28.0 dioptres in the right and left eyes respectively. Unaided visual acuity was 2/60 in both eyes. Fundus examination showed lattice degenerations with a small tear found on both eyes with no retinal detachments. She was treated with a barrage laser on both eyes followed by phacoemulsification. On the last follow-up, the retina remained stable and the visual acuity was significantly improved with no development of macular edema or retinal detachment in both eyes. Discussion : Although most cases of lattice degeneration do not need intervention, some present a risk of retinal detachment. Barrage laser photocoagulation may have a place in high myopic patient lattice degeneration with symptomatic retinal tears to maintain retinal stability and to obtain the optimal outcome after phacoemulsification. Conclusion : Barrage laser photocoagulation is beneficial as a prophylactic treatment of symptomatic retinal tears before phacoemulsification in high-myopic patients.